Mental health and quality of life in patients with craniofacial movement disorders: A cross-sectional study - Yi, Ming; Li, Jing; Liu, Gang; Ou, Zilin; Liu, Yanmei; Li, Jing; Chen, Yicong; Guo, Yaomin; Wang, Ying; Zhang, Weixi; Zeng, Jinsheng; Dang, Chao (Frontiers in Neurology, 2022)
Background: Facial appearance and expressions influence social interaction. Hemifacial spasm (HFS), blepharospasm (BPS), and blepharospasm-oromandibular dystonia (BOD) are common forms of craniofacial movement disorders. Few studies have focused on the mental burden and quality of life (QoL) in patients with craniofacial movement disorders. Therefore, this study investigated mental health and QoL in these patients. Methods: This cross-sectional study included 90 patients with craniofacial movement disorders (HFS, BPS, and BOD; 30 patients per group) and 30 healthy individuals without craniofacial movement disorders (control group) recruited from October 2019 to November 2020. All participants underwent QoL and mental health evaluations for depression, anxiety, and stigma using the 36-item Short Form Health Survey (SF-36), Hamilton Anxiety Rating Scale (HAMA), Hamilton Rating Scale for Depression-24 (HAMD-24) and a questionnaire related to stigma. Results: Depression was diagnosed in 37 (41.11%) patients, whereas 30 patients (33.33%) had anxiety. HAMA scores were significantly higher in the BPS and BOD groups than in the control group. Nineteen patients (21.11%) experienced stigma and SF-36 scores were lower in various dimensions in the movement disorders groups compared to healthy controls. The role-physical and social function scores were significantly lower in the movement disorders groups than in the control group (all p>0.05). The vitality scores of the BPS group and mental health scores of the BPS and BOD groups were significantly lower than those of the control group. Correlation analysis showed that the eight dimensions of SF-36 correlated with education level, disease duration, HAMD score, and HAMA score (all p<0.05). Regression analysis demonstrated that the HAMD score correlated with general health, vitality, social function, role-emotional, and mental health (all p<0.05). The HAMA score correlated with body pain after adjusting for education level and disease duration. Conclusion: This study highlights the significant frequency of mental symptoms, including depression, anxiety, and stigma, which lower QoL in patients with craniofacial movement disorders.